Expression of neprilysin in periodontitis-affected gingival tissues. (July 2017) - Nezu, A.; Kubota, T.; Maruyama, S.; Nagata, M.; Nohno, K.; Morozumi, T.; Yoshie, H.
Highlights: APP and NEP genes were up-regulated in periodontitis-affected gingival tissues. APP expressing cells were confirmed to be macrophages in inflamed gingival tissues. NEP was primarily expressed in neutrophils and fibroblasts in gingival tissues. Abstract: Objective: Although the pathogeneses of Alzheimer's disease (AD) and periodontal diseases have overlapping features, including ageing and chronic inflammation, the association between AD and periodontitis remains unclear. To explore the pathogenesis of periodontitis, a comprehensive gene expression/transcriptome analysis in periodontitis-affected gingival tissues found that the AD pathway was significantly up-regulated in periodontitis-affected gingival tissues. AD-related genes, amyloid beta precursor protein (APP), interleukin-1 beta and compliment 1QA, were significantly elevated in periodontitis. In the present study, balance between mRNA expression of APP and a potent amyloid degradation enzyme, neprilysin (NEP), as well as protein localisation of APP and NEP were analysed. Design: Eighteen periodontitis-affected and 18 clinically healthy control gingival tissues were taken from patients with severe chronic periodontitis or undergoing tooth extraction. Total RNA was purified and used for quantitative reverse transcription real-time polymerase chain reaction (qRT-PCR). The localisation of APP and NEP was analysed by immunohistochemistry (IHC). Results: Both APP and NEP genes were up-regulated in periodontitis-affected gingival tissues. APP-expressing macrophages and NEP-expressing neutrophils and fibroblasts, reflecting inflammatory stages, were detected in inflamed gingival tissues by IHC. Conclusion: The up-regulation of APP and NEP mRNA levels in periodontitis-affected gingival tissues compared with healthy controls was confirmed by qRT-PCR analyses. Since NEP is one of the primary enzymes that degrades amyloid beta, increased NEP mRNA levels in periodontitis may act as an inhibitor of amyloid beta accumulation in gingival tissues, balancing increased APP mRNA expression. However, NEP has several effects including degradation of vasoactive substances; therefore, further sresearch is needed.